Field Study of Imported Lightweight Vehicles Disc Brake Operating Temperature at PLUS Highway Using Infrared Thermography - Jesssica Jatimin; Ismon, Maznan (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Firstly, disc brake systems play a critical role in ensuring vehicle safety by dissipating the heat generated during braking. However, their performance can be significantly affected by operating conditions, particularly in tropical climates. Therefore, this study investigates the thermal behavior of disc brakes in imported Honda vehicles under actual driving conditions along Malaysia’s PLUS Highway. Specifically, the main objective is to analyze temperature distribution and identify potential thermal stress using a non-contact, real-time method. To achieve this, a FLIR T640 infrared thermography camera was used to capture thermal images of the disc brakes at the Yong Peng Utara toll area during various times of the day. As a result, the findings revealed distinct temperature variations influenced by braking frequency, vehicle speed, and ambient conditions, with noticeable hotspots forming during repeated braking events. In conclusion, the study demonstrates the effectiveness of infrared thermography in evaluating brake performance and highlights its potential in improving brake system design, material selection, and overall vehicle safety in tropical road environments.